Implementation of 16S rRNA Gene for Fish and Shrimp Barcoding in Mangrove Ecosystems in North Sumatra and Aceh, Indonesia - Hatika Hairani; Rizka Amelia; Ipanna Enggar Susetya; Arida Susilowati; Yuntha Bimantara; Tadashi Kajita; Mohammad Basyuni (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research